A Turn-off Fluorescent Chemosensor for Detecting Formaldehyde Based on Pyridine Derivative - Hidayah, Nurul; Purwono, Bambang (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Formaldehyde in solution, commonly known as formalin, is often utilized. In Indonesia, there is widespread misuse of formalin as a food preservative. Formaldehyde has been identified as a carcinogenic substance by the International Agency for Research on Cancer (IARC) and the Environmental Protection Agency (EPA). Based on this background, the present study developed a sensor compound capable of detecting formaldehyde obviously. The compound 3'-(4-(3,4-dimethoxyphenyl)pyridine-2,6-diyl)dianiline (ChP-2A) has been successfully synthesized through the reduction reaction of the compound 4-(3,4-dimethoxyphenyl)-2,6-bis(3-nitrophenyl)pyridine (ChP-0A) using 80% hydrazine hydrate and 10% Pd/C as a catalyst. The ChP-2A compound in acetonitrile exhibits a significant decrease in fluorescence intensity (turn-off) after the addition of formaldehyde, and it has been successfully applied in the form of a test paper for the detection of formaldehyde qualitatively